Salbutamol exhibits androgenic activity in vitro - von Bueren, A. O.; Ma, R.; Schlumpf, M.; Lichtensteiger, W. (British Journal of Sports Medicine, 2007)
Background: Salbutamol has been shown to mediate anabolic effects after intravenous administration. However, the mechanism responsible for the anabolic actions of salbutamol remains unknown.